Melanoma central nervous system metastases: An update to approaches, challenges, and opportunities. (19th February 2019) - Eroglu, Zeynep; Holmen, Sheri L.; Chen, Qing; Khushalani, Nikhil I.; Amaravadi, Ravi; Thomas, Reena; Ahmed, Kamran A.; Tawbi, Hussein; Chandra, Sunandana; Markowitz, Joseph; Smalley, Inna; Liu, James K. C.; et al.
Abstract: In February 2018, the Melanoma Research Foundation and the Moffitt Cancer Center hosted the Second Summit on Melanoma Central Nervous System (CNS) Metastases in Tampa, Florida. In this white paper, we outline the current status of basic science, translational, and clinical research into melanoma brain metastasis development and therapeutic management. We further outline the important challenges that remain for the field and the critical barriers that need to be overcome for continued progress to be made in this clinically difficult area.